Teachers’ Influence on Students’ Mathematics Performance in Zamfara State: Implication for Classroom Practice - Abubakar Kabiru Tsafe; Saidu Isa Babangida; Lawal Chafe Ahmad; Bashir Mustapha (Journal of Instructional Mathematics, 2024)
The purpose of this research was to examine the influence of some teacher variables on students’ mathematics performance in Zamfara state. Three objectives, research questions and null hypotheses were formulated to guide the study. A quasi-experimental design was used with a non-randomized sample of three hundred and seventy nine (N=379) students was drawn and distributed over four schools that were purposively selected. Mathematics Teacher Variable Test (MTVT) was used in the collection of data. Mean, standard deviation, and mean difference were for descriptive analysis, while t-test was for inferential analysis. Findings of the study revealed that the influence of teacher variables was tremendous. For instance, students taught by teachers with higher qualifications performed better than their counterparts taught by teachers with lower qualifications. Similarly, years of experience played a vital role in students’ performance in mathematics better than teachers who are relatively new in the teaching profession. Gender was also found to have influence on students’ performance because students taught by male teachers had better performance than their counterparts taught by female teachers. In the end, the study recommends amongst others, the need for sponsoring teachers with lower qualifications to go for in-service training in order to acquire higher qualifications.